Effect of Addition AgNO3 on some Optical Properties of Polystyrene (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In the present work, effect of addition AgNO3 on some optical properties of polystyrene has been studied. for that purpose, many samples has been prepared by adding AgNO3 on the polystyrene by different volume percentages from these salts with polymer and by different thickness.The absorption and transmission spectra has been recorded in the wavelength range (190-1100)nm. The absorption coefficient and energy gap of the indirect, allowed, forbidden transition have been determined.